Chlamydia trachomatis Biovar L2 Infection in Women in South Africa - Remco P.H. Peters; Ronan Doyle; Mathys J. Redelinghuys; James A. McIntyre; Georges M. Verjans; Judith Breuer; Marleen M. Kock (Emerging Infectious Diseases, 2017)
We detected Chlamydia trachomatis biovar L2 in vaginal swab specimens of 7 women with vaginal discharge in South Africa. Whole-genome sequencing directly from clinical specimens identified a closely related cluster of strains. The clinical role of this infection in the context of syndromic management should be clarified.